Miti ter znanstveno podprti dokazi o smislu in možnosti vplivanja na kislinsko-bazno in elektrolitsko homeostazo človeškega organizma - Jeras, Matjaž (Farmacevtski vestnik, 2017)
Because of very precise and relatively robust life-supporting regulation of physiological pH and electrolyte composition of blood, the claims that the human organism can be deacidified by consuming alkaline diet and food supplements, which would in turn improve health and prevent some diseases or ameliorate their courses, is highly questionable. In this article we describe basic homeostatic mechanisms that provide maintenance of acid-base and electrolyte equilibria, as well as some pathologies caused by their malfunctions. Then we present the results of critical literature reviewing carried out to find any kind of scientifically confirmed proofs regarding disease-preventing or disease-improving benefits being attributed to consumption of alkaline foods and nutrient supplements. We conclude that currently there is no scientific evidence available to back-up these claims.
Keywords: alkalna prehrana; elektroliti; homeostaza; kislinsko-bazno razmerje; razkisanje organizma